Amazon forest response to repeated droughts. Issue 7 (1st July 2016) - Feldpausch, T. R.; Phillips, O. L.; Brienen, R. J. W.; Gloor, E.; Lloyd, J.; Lopez‐Gonzalez, G.; Monteagudo‐Mendoza, A.; Malhi, Y.; Alarcón, A.; Álvarez Dávila, E.; Alvarez‐Loayza, P.; Andrade, A.; et al.
Abstract: The Amazon Basin has experienced more variable climate over the last decade, with a severe and widespread drought in 2005 causing large basin‐wide losses of biomass. A drought of similar climatological magnitude occurred again in 2010; however, there has been no basin‐wide ground‐based evaluation of effects on vegetation. We examine to what extent the 2010 drought affected forest dynamics using ground‐based observations of mortality and growth from an extensive forest plot network. We find that during the 2010 drought interval, forests did not gain biomass (net change: −0.43 Mg ha −1, confidence interval (CI): −1.11, 0.19, n  = 97), regardless of whether forests experienced precipitation deficit anomalies. This contrasted with a long‐term biomass sink during the baseline pre‐2010 drought period (1998 to pre‐2010) of 1.33 Mg ha −1  yr −1 (CI: 0.90, 1.74, p  < 0.01). The resulting net impact of the 2010 drought (i.e., reversal of the baseline net sink) was −1.95 Mg ha −1  yr −1 (CI:−2.77, −1.18; p  < 0.001). This net biomass impact was driven by an increase in biomass mortality (1.45 Mg ha −1  yr −1 CI: 0.66, 2.25, p  < 0.001) and a decline in biomass productivity (−0.50 Mg ha −1  yr −1, CI:−0.78, −0.31; p  < 0.001). Surprisingly, the magnitude of the losses through tree mortality was unrelated to estimated local precipitation anomalies and was independent of estimated local pre‐2010 drought history. Thus, there was no evidence that pre‐2010 droughts compounded the effects of the 2010 drought. We detected a systematic basin‐wide impact of the 2010 drought on tree growth rates across Amazonia, which was related to the strength of the moisture deficit. This impact differed from the drought event in 2005 which did not affect productivity. Based on these ground data, live biomass in trees and corresponding estimates of live biomass in lianas and roots, we estimate that intact forests in Amazonia were carbon neutral in 2010 (−0.07 Pg C yr −1 CI:−0.42, 0.23), consistent with results from an independent analysis of airborne estimates of land‐atmospheric fluxes during 2010. Relative to the long‐term mean, the 2010 drought resulted in a reduction in biomass carbon uptake of 1.1 Pg C, compared to 1.6 Pg C for the 2005 event. Key Points: During the 2010 drought interval, Amazon forests did not gain biomass, regardless of whether forests experienced precipitation deficit anomalies Biomass losses were partially driven by a decline in productivity related to precipitation anomalies Pre‐2010 droughts did not compound the effects of the 2010 drought